Konflik Batin Tokoh Utama Dalam Novel Lemon Tea Candy Karya Nunu Gie: Kajian Psikologi Sastra Dan Implementasinya Sebagai Bahan Ajar Sastra Di Smp - Dewi, Ririk Novitasari Rahma (2016)
This research aimed at describing the social-historical background of NunuGie, the structure that built the novel Lemon Tea Candywritten byNunuGie, the inner conflict and the personality of the main actor in the novel Lemon Tea Candywritten byNunuGiein the effort of improving the life and reaching the dream viewed from the Literary Psychology, and the implementation ofthe inner conflict in the novel Lemon Tea Candywritten byNunuGieas the teaching material in Junior High School (SMP). This research used a descriptive qualitative method. The object of research was the novel Lemon Tea Candywritten byNunuGie. The primary data source of this research was the inner conflict in the novel Lemon Tea Candy, and the secondary data source was the internet website. The technique of data collection in this research used the library technique and taking a note. Triangulations used in this research were the data triangulation and theory triangulation. The techniques ofdata analysis in this research were semiotics, heuristics and hermeneutics. The results of the research on the inner conflict of the main actor in the Novel Lemon Tea Candy: A Literary Psychology Study were: the social-historical background of NunuGiewas known as a new writer with the writing characteristics of having a theme about social life in general and moral teaching in his works. The novel structure which consisted of elements such as theme, plot, actors, setting of place, setting of time, and social setting showed integrity orharmonyin supporting the meaning of the novel. The inner conflict in the novel Lemon Tea Candy includedconflict ofapproaching-approaching, conflict of approaching-staying away, and conflict of staying away-staying away. The implementations of Competence Standard and Basic Competenceon the novel materialcould be seen in SK. 14 (Competence Standard 14): Appreciating the quotations oforiginal teenagernovel or translation novel through an activity of discussion, and KD. 14.1 (Basic Competence 14.1): Commenting on the quotations ofteenager novel (original or translation) in SMP Class VIII Semester 2.